Bimbingan Teknis Peningkatan Produksi Krupuk dan Kripik dengan Mesin Pengiris Bagi Usaha Mikro di Kota Semarang - Eddy Prabowo, Rokh; Yunianto , Askar; Fauzan , Muhammad; Anggana L, Gregorius (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
In general, home industries face similar problems, such as soybean sago tempeh craftsmen, cracker and various chip craftsmen in the city of Semarang. Problems faced include low production volumes, high operational costs. Currently, cracker and chip craftsmen still use simple tools, so production is less than optimal. Apart from that, there is the problem of difficulty in accessing financial resources and expensive slicing machines. The aim of this service program is to provide training to increase the quantity and quality of chip and cracker production. The stages of this service program include needs analysis, design, assistance and implementation, and evaluation. The targeted chip and cracker craftsmen were given training. The result of this activity is to increase the production of chips and crackers both in terms of product quantity and quality. Another result is that craftsmen can calculate the cost of purchasing a slicing machine.